Hypofractionated radiotherapy with simultaneous-integrated boost after breast-conserving surgery compared to standard boost-applications using helical tomotherapy with TomoEdge - Zwicker, Felix; Hoefel, Sebastian; Kirchner, Corinna; Huber, Peter E.; Debus, Jürgen; Schempp, Michael (Anticancer research, 2021)
Background/Aim: This comparative plan study examines a range of boost-radiation methods in adjuvant radiotherapy of breast cancer using helical intensity-modulated radiotherapy with TomoEdge-technique. Impact of hypofractionated radiation with simultaneous-integrated boost (SIB) and influence of differing assumed α/β-values were examined. Patients and Methods: For 10 patients with left-sided breast cancer each four helical IMRT-plans with TomoEdge-technique were created: hypofractionated+SIB (H-SIB) (42.4/54.4 Gy, 16 fractions), normofractionated+SIB (N-SIB) (50.4/64.4 Gy, 28 fractions), hypofractionated+sequential-boost (H-SB) (42.4 Gy/16 fractions+16 Gy/8 fractions), normofractionated+ sequential-boost (N-SB) (50.4 Gy/28 fractions+16 Gy/8 fractions). Equivalent doses (EQD2) to organs-at-risk (OAR) and irradiated mammary-gland were analysed for different assumed α/β-values. Results: The mean EQD2 to OAR was significantly lower using hypofractionated radiation-techniques. H-SIB and H-SB were not significantly different. H-SIB and N-SIB conformed significantly better to the breast planning-target volume (PTV) and boost-volume (BV) than H-SB and N-SB. Regarding BV, mean EQD2 was significantly higher for all α/β-values investigated when using H-SIB and N-SIB. Regarding PTV, there were no clinically relevant differences. Conclusion: Relating to dosimetry, H-SIB is effective compared to standard-boost-techniques.